Modeling Microbial Behavior and Ecotoxicological Effects in Thermal Radiation MHD Casson Fluid Flow Over a Stretching Sheet: Multilinear Regression and Streamline Analysis with Non-Uniform Source Effects (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This study investigates microbial behavior and ecotoxicological impacts in thermal radiation magnetohydrodynamic (MHD) Casson fluid flow over a stretching sheet. The study incorporates non-uniform source effects, highlighting its relevance to biological systems and industrial applications. A hybrid approach combining multilinear regression and streamline analysis is utilized to explore the relationship between key system parameters—including magnetic field strength, thermal radiation, and non-uniform sources—and microbial behavior. Numerical simulations analyze temperature, velocity, and concentration fields to assess their impact on microbial growth and distribution. The findings indicate significant influences of thermal radiation, magnetic fields, and non-uniform sources on microbial behavior, emphasizing the importance of ecotoxicological considerations. This study introduces a novel integration of multilinear regression and streamline analysis to enhance pollutant transport modeling, providing valuable insights for environmental and industrial applications.